UV-Blocking, Transparent, and Antioxidant Polycyanoacrylate Films - Quilez-Molina, Ana Isabel (Polymers (Basel), 2020)
Applications of cyanoacrylate monomers are generally limited to adhesives/glues (instant or superglues) and forensic sciences. They tend to polymerize rapidly into rigid structures when exposed to trace amounts of moisture. Transforming cyanoacrylate monomers into transparent polymeric films or coatings can open up several new applications, as they are biocompatible, biodegradable and have surgical uses. Like other acrylics, cyanoacrylate polymers are glassy and rigid. To circumvent this, we prepared transparent cyanoacrylate films by solvent casting from a readily biodegrade solvent, cyclopentanone. To improve the ductility of the films, poly(propylene carbonate) (PPC) biopolymer was used as an additive (maximum 5 wt.%) while maintaining transparency. Additionally, ductile films were functionalized with caffeic acid (maximum 2 wt.%), with no loss of transparency while establishing highly effective double functionality, i.e., antioxidant effect and effective UV-absorbing capability. Less than 25 mg antioxidant caffeic acid release per gram film was achieved within a 24-h period, conforming to food safety regulations. Within 2 h, films achieved 100% radical inhibition levels. Films displayed zero UVC (100–280 nm) and UVB (280–315 nm), and ~15% UVA (315–400 nm) radiation transmittance comparable to advanced sunscreen materials containing ZnO nanoparticles or quantum dots. Transparent films also exhibited promising water vapor and oxygen barrier properties, outperforming low-density polyethylene (LPDE) films. Several potential applications can be envisioned such as films for fatty food preservation, biofilms for sun screening, and biomedical films for free-radical inhibition.